Pollen characters as taxonomic evidence in some species of Dipsacaceae from Iran (Bangladesh Journal of Plant Taxonomy, 2017)
Pollen morphology of nine species representing four genera: Cephalaria Schrad, Dipsacus L., Pterocephalus Vaill. and Scabiosa L. of the family Dipsacaceae in Iran has been investigated by means of scanning electron microscopy (SEM). The results showed that pollen grains were triporate and tricolpate. The pollen type of Scabiosa rotata Bieb. (tri- and tetraporate) is the first report in the world. The sizes of pollen grains fall into the classification group magna (pollen grain diameter 50–100 μm). Pollen shapes vary from preoblate to prolate and their polar views were triangulate and lobate. The exine ornamentation varies from gemmate in S. rotata to spinulate in the rest studied species. Species of Scabiosa have been dispersed in UPGMA tree that this confirmed the previous studies about taxonomic problems and species complexity in this genus. These results show the transfer of the some Scabisoa species to Lomelosia Raf. based on palynological characters. Pollen morphology of the family is helpful at the generic and specific level.Bangladesh J. Plant Taxon. 24(2): 129–136, 2017 (December)